MULITA: UNA NUEVA HERRAMIENTA PARA EL APRENDIZAJE DE LA TECNOLOGÍA Y EL PENSAMIENTO COMPUTACIONAL - Javier Calderón , Sebastián; Javier da Silva Gillig, Octavio; Cecilia Tumino , Marisa; Manuel Bournissen, Juan (Revista Formadores, 2023)
.